Expression and characterization of PrnC—a flavin-dependent halogenase from the pyrrolnitrin biosynthetic pathway of Pseudomonas protegens Pf-5 - Gebauer, Jan; Pietruszka, Jörg; Classen, Thomas (Frontiers in Catalysis, 2023)
The antimicrobial pyrrolnitrin from Pseudo¬monas strains is formed in four steps from tryptophan and comprises two flavin-dependent halogenases. Both PrnC and PrnA can carry out regioselective chlorination and bromination and are carrier protein-independent.Both carrier protein-independent halogenases carry out regioselective halogenations with chloride and bromide, respectively. Whilst the tryptophan halogenase PrnA has been studied in detail in the past, this study focusses on the pyrrole halogenating enzyme PrnC. This enzyme as well as the essential electron suppliers, the flavin reductases, have been produced soluble in E. coli. Furthermore, a screening of a rational compound library revealed that the pyrrole is essential for substrate recognition; however, the substitution pattern of the benzene ring is not limiting the catalysis. This renders PrnC to be a synthetically valuable enzyme for the synthesis of pyrrolnitrin congeners. For its natural substrate monodechloroaminopyrrolnitrin (MDA) the KM value was determined as 14.4 ± 1.2 µM and a kcat of 1.66 ± 0.02 min -1 , which is comparable to other halogenases.